Utilization of raw coal gangue as coarse aggregates in pavement concrete. (16th May 2023) - Zhao, Hui; Wang, Shuaifeng; Wang, Rui; Shen, Linghua; Wang, Qinghe
Highlights: Mechanical and durability behaviors of pavement concrete using raw coal gangue aggregate (RCGA) Effects of RCGA replacements (0%, 30% and 50%) and w / c ratios (0.36, 0.45) The higher the RCGA content, the lower mechanical and durability properties of concrete. Microstructures of RCGA concrete subjected to freeze–thaw. Abstract: A large amount of raw coal gangue (RCG) is generated during coal mining, which results in serious environmental problems and vast land occupation. Considering the similarity between RCG and natural aggregates, the mechanical and durability behaviors of pavement concrete using raw coal gangue aggregate (RCGA) as coarse aggregates are investigated in this work. A total of 396 samples were produced with three RCGA ratios of 0%, 30% and 50% and two water-to-cement ( w / c ) ratios of 0.36 and 0.45. The fluidity, compressive, splitting tensile and flexural strengths, modulus of elasticity, abrasion, impermeability, as well as freeze–thaw resistance (water and de-icing salt) of RCGA concrete were obtained, and the microstructures were analyzed to investigate the freeze–thaw damage to concrete. Experimental results indicated that the RCGA presented a negative influence on the mechanical and durability properties of concrete. The higher the RCGA content, the lower the strengths and elastic modulus, and the more the degradations of the abrasion, impermeability, and freeze–thaw resistance of concrete. In addition, the microstructures showed that the interfacial transition zone (ITZ) between RCGA and cement paste was the weak area of concrete. Results demonstrated that concrete containing 30% RCGA can be employed in the tertiary pavement under both freeze–thaw and deicing salt conditions following code JTG 3420-2020.